Peran Mahasiswa Kkn Unp Dan Pemerintah Desa Batu Tanjung Dalam Penguatan Literasi Melalui Pendampingan Penilaian Perpustakaan - Muhammad Fahrur Rozi; Shakhira Novita Anggraini; Anisa Rilma Yuliani; Mozza Tursina Anha; Tiara Rahmadini (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This article discusses the collaboration between students of Universitas Negeri Padang's Community Service Program (KKN) and the Batu Tanjung Village Government to strengthen community literacy through library assessment assistance. The challenges identified in this activity are low community participation and limited library facilities. In this research, the author raises issues with a literature study approach using descriptive-qualitative methods. In KKN activities, students are responsible for library organization, classifying books with DDC, and creating an attractive reading atmosphere. At the same time, the village government participated in the provision of facilities, arrangements, as well as policies and program sustainability. The results showed that a balanced collaboration between students and the village government was beneficial in developing a sustainable and dynamic literacy culture.